A qualitative report of children’s and youth well-being in greece in a time of crisis - Κορωναίου Αλεξάνδρα; Αλεξιάς Γεώργιος; Χιωτάκη-Πούλου Ειρήνη; Βάγιας Γεώργιος Χ. (The Greek Review of Social Research, 2017)
The article presents the findings of a survey on children’s and youth well-being and quality of life, as part of the European research programme MYWEB (Measuring Youth Well-Being). The qualitative approach of the survey employing the appropriate research methods (interviews and focus groups) aims to highlight the way children and young people perceive these concepts and the factors they value for their well-being and their future in a period of crisis. It is concluded that well-being is a combination of psychological and social conditions and that it is essential the children’s and youth voice is heard particularly by those engaged in political decision-making in order to tackle the crisis and the subsequent social inequalities.